Health care criteria for performance excellence: a case study of Klinik Rawatan Keluarga (KRK) / Roslida Abdul Razak ... [et al.] - Abdul Razak, Roslida; Aziz, Rahimah; Mamat, Alias; Mat Yusof, Mohd Husnin (2007)
Klinik Rawatan Keluarga (KRK), is a private hospital which offer an Obstetrics and Gynecology (O&G) service beside normal treatment. KRK managed by Dr Wan Razani Wan Mohamad, a former government servant. It has 8 full time staffs with three part time professional doctors. Surrounding by three major competitors, KRK is still able to sustain its business. However, the owner never studies how far her business had performed and never had a complete study to analyze her health care business. This has caught our intention to perform a study on KRK performance particularly in service delivery. The vital problem which taken into accounts in our study are studying the service variables in order to ensure high quality service being rendered and the financial performance did not show a tremendous upward achieving but only at similarity level. Benchmarking is one of the tools to measure quality. Malcom Baldrige criteria have been implemented to measure KRK performance against world recognized standard. Since KRK is a profit oriented organization, financial performance is inevitable to ignore. For the past 6 years KRK financial performance does not present much improvement. We believed our case study will improve the quality consequently picking-up its financial performance. Malcom Baldrige has seven criteria to converge namely, i. Leadership, ii. Strategic planning, iii. Focus on patient, iv. Measurement analysis, v. workforce focus, vi. Process Management, and vii. Result disclosed. 2 approaches have been implemented specifically through questionnaire distribution through both staff and out-patient and its owner personal interview. Both methods are analyzing through Statistical Package for Social Science and Malcom Baldrige weighted points respectively. From our study, leadership score 62 out of 120 or 51.67%. Strategic planning score 53 or 62.35%, process management score 85 or 48.24% and measurement analysis carried 45 or 50%. The focus on patient and workforce focus show (SPSS results are significant). From Malcom Baldrige and our observation, it is reveal that KRK be in the position of hold and maintain of its operation. Beside that, the key growth rate, for the most part in sales and net income for the past 5 years show an average of 2.56 percent and negative 9.01 percent respectively. Due to that, we have suggested several recommendations as mention in the study.